Life imprisonment in Malaysia: prospects for law reform? - Dusuki, Farah Nini (Life Imprisonment in Asia, 2023)
Life imprisonment in Malaysia has two divergent meanings, and is used in different forms as punishment for serious offences. As the death penalty exists, both in mandatory and discretionary modes, life imprisonment caters for the comparatively less serious offences than those that are punishable with death. Although efforts are currently underway to abolish the mandatory death penalty, this change will only be realised in the future. This chapter examines these issues, including the different meanings and forms of life imprisonment, statutorily and in practice, and discusses their implementation against the backdrop of the international legal framework.